Prevalence of livestock diseases and their impact on livelihoods in Central Equatoria State, southern Sudan - Malak, Agol K.; Mpoke, L.; Banak, J.; Muriuki, S.; Skilton, Robert A.; Odongo, D.; Sunter, J.; Kiara, Henry K. (Elsevier, 2012)
A participatory epidemiological (PE) study was conducted in Kajo Keji and Yei Counties, Central Equatoria State, southern Sudan to assess the impact of livestock diseases on livelihoods. A serological survey of tick-borne diseases was conducted to supplement the PE study. PE data collection tools consisted primarily of focus group interviews and key informant interviews supplemented by observation. Information was collected on the social context, history and species of livestock kept. Constraints in livestock keeping were explored through description and probing. Proportional piling on the importance of different diseases and relative incidence scoring were also conducted. 243 sera were collected from cattle and tested for antibodies to Anaplasma marginale, Babesia bigemina, B. bovis, Theileria mutans and T. parva by ELISA. Additionally, 173 blood samples were collected for a PCR assay of T. parva. Livestock diseases were ranked as the most important constraint to livestock keeping. While East Coast fever was ranked as the most important disease in Kajo Keji, diarrhoea in small ruminants was reported as the most important disease in Yei. Serological analyses of the sera indicated that A. marginale, B. bigemina, T. mutans and T. parva were most prevalent. Prevalence of B. bovis was found to be low (4.0% and 7.4% in Kajo Keji and Yei, respectively). 35% of the samples screened with the T. parva p104 gene nested PCR assay were positive. The study concludes that while ECF is the most important disease in Kajo Keji, it was not the case in Yei. Additional epidemiological studies are proposed before control strategies are recommended.